2021
DOI: 10.1029/2021jb022106
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Crystal Growth in Single‐Seal Syntaxial Veins in Limestone ‐ A Phase‐Field Study

Abstract: The chemistry and mechanics of fracture sealing in deforming hydrothermal and reactive environments is important in basic geoscience and applied studies. Examples are the seismic cycle (e.g., Alexandrakis et al., 2014), evolution of ore deposits (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(166 reference statements)
0
9
0
Order By: Relevance
“…13a). This is the classical syntaxial vein geometry in which the crystals typically have blade-like or elongate-blocky shapes (Durney & Ramsay, 1973;Fisher & Brantley, 1992;Hilgers et al 2001;Okamoto & Sekine, 2011;Späth et al 2021). Although the original work of Ramsay (1980) and many other subsequent papers assume that the whole crack fills with minerals before the next crack event, this is not always the case, especially under diagenetic conditions.…”
Section: B Veins As Potential Fossil Hydrofracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…13a). This is the classical syntaxial vein geometry in which the crystals typically have blade-like or elongate-blocky shapes (Durney & Ramsay, 1973;Fisher & Brantley, 1992;Hilgers et al 2001;Okamoto & Sekine, 2011;Späth et al 2021). Although the original work of Ramsay (1980) and many other subsequent papers assume that the whole crack fills with minerals before the next crack event, this is not always the case, especially under diagenetic conditions.…”
Section: B Veins As Potential Fossil Hydrofracturesmentioning
confidence: 99%
“…He showed that veins can form by repeated failure that results in opening of a fracture (the 'crack' stage), and subsequent filling of the fluidfilled space with minerals (the 'seal' stage). Mineral precipitation is usually by epitaxial overgrowth of mineral grains at the fracture surfaces, as can be seen from the optical continuity between old and new growth stages (Urai et al 1991;Laubach et al 2004;Späth et al 2021). A crack-sealing cycle can occur once for a vein, but also many times, each time adding a slice of mineral precipitate to the widening vein.…”
Section: B Veins As Potential Fossil Hydrofracturesmentioning
confidence: 99%
“…Chen, 2002; Choudhury, 2017; Fix, 1982; Langer, 1980, 1986). The methodology has also emerged as a prominent computational method for modeling diverse geological processes, such as mineral cementation (Prajapati, Abad Gonzalez et al., 2020; Prajapati et al., 2017; Prajapati, Selzer, Nestler, Busch, Hilgers, et al., 2018), fracture propagation in sandstone (Prajapati, Herrmann, et al., 2020), and formation of crack‐seal morphologies such as quartz veins (Ankit et al., 2013; Ankit, Urai, & Nestler, 2015; Ankit, Selzer, et al., 2015; Späth et al., 2022a, 2022b; Wendler et al., 2016) and calcite veins (Prajapati, Selzer, Nestler, Busch, & Hilgers, 2018; Späth et al., 2021; Spruženiece et al., 2020, 2021). Further, mineral dissolution processes have been modeled using PFM in one dimension (1D) (Xu & Meakin, 2008) and two dimensions (2D) (Bringedal et al., 2020; Xu et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, its implications on the resulting permeability are difficult to estimate, as the generated pores may remain isolated (Pittman, 1979). Using digital rocks and novel modeling techniques (Monsees et al., 2020; Prajapati, Abad Gonzalez et al., 2020; Späth et al., 2021) one can assess the specific contribution of feldspar dissolution on permeability. Numerical modeling of geological processes has been playing a dominant role to gain insights, that are normally unavailable through laboratory experiments and field observations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, increased understanding of calcite cement growth has been made by structural geologists (Bons et al, 2012;Hilgers & Urai, 2002;Lander et al, 2008;Lander & Laubach, 2015;Nollet et al, 2005Nollet et al, , 2006Roberts et al, 2020). Their modelling of blocky cement in static syntaxial veins (Späth et al, 2021;Spruženiece et al, 2021) is directly applicable to pore filling cements.…”
Section: Introductionmentioning
confidence: 99%